2020
DOI: 10.1002/nop2.586
|View full text |Cite
|
Sign up to set email alerts
|

Single‐room maternity care: Systematic review and narrative synthesis

Abstract: Single-room maternity care (SRMC)-also known as labour-delivery-recovery-postpartum (LDRP) care-was developed as an alternative to the traditional labour and delivery suites during the family-centred care movement, which promoted birth as a normal family process (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…Having privacy and their partner's presence was essential for mothers in order to create a family. Mothers mentioned the importance of having a single room, which was also appreciated in another study reporting higher care satisfaction when in a single room ( 55 ). Mothers in our study reported the partner's presence as important to co-construct their parenting together.…”
Section: Discussionmentioning
confidence: 74%
“…Having privacy and their partner's presence was essential for mothers in order to create a family. Mothers mentioned the importance of having a single room, which was also appreciated in another study reporting higher care satisfaction when in a single room ( 55 ). Mothers in our study reported the partner's presence as important to co-construct their parenting together.…”
Section: Discussionmentioning
confidence: 74%
“…Our synthesis approach for objective 1 to a greater part will take the form of a narrative synthesis [56,57]. Other studies have been found to use a similar method [58][59][60][61]. This will help maintain the contextual nature of the different mass testing options that will emanate from the literature.…”
Section: Synthesis Proceduresmentioning
confidence: 99%
“…This data may not reflect the experiences in other locations. Despite these limitations, this study addresses important gaps in the literature, including the examination of readiness for discharge, calculations of effect size, multivariate statistical analysis in modelling predictors, and the inclusion of covariates, all of which have been very limited or are not discussed at all in the existing literature (Ali et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%
“…The intrapartum and postpartum units have their own separate staff since nurses specialize in one type of maternity care (Stolte et al, 1994). One study of SRMC found that nurses described practices as relational and patient-centered where teaching, care, and support of families was apparent in every stage of the childbirth process (Ali et al, 2019). In contrast, in a study comparing SRMC and TMC units, providers described TMC as having a fragmentation of care and breakdown in communication and discharge planning (Hall et al, 2019).…”
Section: Background and Purposementioning
confidence: 99%
See 1 more Smart Citation